Creditor Passivity: The Effects of Bank Competition and Institutions on the Strategic Use of Bankruptcy Filings - Christa Hainz (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
Why do banks remain passive? In a model of bank-firm relationship we study the trade-off a bank faces when having defaulting firms declared bankrupt. First, the bank receives a payoff if a firm is liquidated. Second, it provides information about a firm's type to its competitors. Thereby, asymmetric information between banks is reduced and bank competition intensifies. We find that the better the institutions and the more competitive the banking sector, the higher the bank's incentive to bankrupt defaulting firms. This makes information between banks less asymmetric and thus leads to lower interest rates and less credit rationing.
urn:nbn:de:bvb:19-epub-2028-7
Keywords: G21; G33; K10; D82; 330; Creditor passivity; bank competition; information sharing; institutions; bankruptcy; relationship banking; Insolvenz; Informationsverbreitung; Gläubiger; Institutionelle Infrastruktur; Unvollkommener Wettbewerb; Bank; Theorie; Transformationsstaaten